Pengaruh Kualitas SDM, Profesionalisme Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di PT. Kraft Heinz ABC - Novita Rahayu Mone (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the influence of determinants of human resource quality, work professionalism and work motivation on improving employee performance at PT. Kraft Heinz ABC. The number of samples in this study is 41 respondents who are employees of PT. Kraft Heinz ABC where with the saturated sample method. The data collection method is by means of observation, interviews, documentation studies and questionnaires. The data analysis techniques used are research instrument tests, classical assumption tests, multiple linear regression analysis, simultaneous tests (F-test) and partial tests (t-tests). The results of this study are that the quality of human resources has a significant positive effect on employee performance at PT. Kraft Heinz ABC. Work professionalism has a significant positive effect on employee performance at PT. Kraft Heinz ABC. Work motivation has a significant positive effect on employee performance at PT. Kraft Heinz ABC. The quality of human resources, work professionalism and work motivation together affect employee performance at PT. Kraft Heinz ABC. Suggestions that can be given are adjusting the employee's work position, working according to SOPs, providing rewards for employees so that they can improve employee performance.